Effect of sample area in reverberant chamber measurements of sound absorption coefficients - António P. O. Carvalho (2016)
To evaluate the influence of the sample size on the experiments in a reverberant chamber to determine the sound absorption coefficient, the reasonable minimum sample area needed was analyzed, considering that the quantity of material is important for those who want to test it. Samples from 1 to 12 m2 (by increments of 1 m2 ) were used. The influence of the sample position on the room's floor has also been tested for a 10 m2 sample arranged on the center of the reverberating chamber and scattered around the room.